PHILIP MORRIS' POSITION ON ACCOMMODATION (Tufts Archival Research Center, 2007)
Document outlining Philip Morris' position on accommodating smokers in public places. Acknowledges the annoyance that second hand smoke can be but says that a smoking ban is not a good answer as it creates many problems as well.